2023
DOI: 10.3897/mycokeys.97.102653
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and molecular analyses reveal three new species of Botryosphaeriales isolated from diseased plant branches in China

Abstract: The Botryosphaeriales represents an ecologically diverse group of fungi, comprising endophytes, saprobes, and plant pathogens. In this study, taxonomic analyses were conducted based on morphological characteristics and phylogenetic analyses of multi-gene sequence data from four loci (ITS, LSU, tef1-α, and tub2). Thirteen isolates obtained from Beijing and Yunnan Province were identified as seven species of Botryosphaeriales, including Aplosporella javeedii, Dothiorella alpina, Phaeobotryon aplosporum and Ph. r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…Studies on Botryosphaeriaceae, dealing with the phylogenetic traits and morphology of isolates associated with various hosts, have increased in recent years, enabling the worldwide identification of taxa at the species level [2,5,18,[45][46][47][48][49]. In this study, 16 Botryosphaeriaceae isolates were obtained from several decaying woody hosts (dead arial twigs, branches, stems, bark, and seed pods) in southwestern China and northern Thailand, and they were identified as 11 species based on a polyphasic approach of morphological features and molecular phylogeny.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on Botryosphaeriaceae, dealing with the phylogenetic traits and morphology of isolates associated with various hosts, have increased in recent years, enabling the worldwide identification of taxa at the species level [2,5,18,[45][46][47][48][49]. In this study, 16 Botryosphaeriaceae isolates were obtained from several decaying woody hosts (dead arial twigs, branches, stems, bark, and seed pods) in southwestern China and northern Thailand, and they were identified as 11 species based on a polyphasic approach of morphological features and molecular phylogeny.…”
Section: Discussionmentioning
confidence: 99%
“…Dothiorella was introduced by Saccardo [53] with Do. pyrenophora as the type species, and presently, only 38 species are accepted in this genus based on phylogenetic analyses [16,18,49]. Zhang et al [48] made a systematic revision of Dothiorella by synonymizing 15 known species, which reduced the number of Dothiorella members and established a more stable systematic relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequences obtained were assembled using SeqMan v. 7.1.0 software, and reference sequences from related publications (Phillips et al 2019;Lin et al 2023a;Wu et al 2023) were retrieved from the National Center for Biotechnology Information (NCBI; https://www.ncbi.nlm.nih.gov).…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…Pan et al (2019) found that Phaeobotryon rhois and Diplodia quercicola were detrimental to Rhus typhina and Quercus variabilis separately in Yudu Mountain, Beijing. Aplosporella yanqingensis and Dothiorella baihuashan are mainly recorded on Pinaceae or Cupressaceae (Lin et al 2023a). Lasiodiplodia regiae caused the canker and dieback of apple trees (Wang et al 2023).…”
Section: Introductionmentioning
confidence: 99%